2013
DOI: 10.1093/nar/gkt892
|View full text |Cite
|
Sign up to set email alerts
|

Human snRNA genes use polyadenylation factors to promote efficient transcription termination

Abstract: RNA polymerase II transcribes both protein coding and non-coding RNA genes and, in yeast, different mechanisms terminate transcription of the two gene types. Transcription termination of mRNA genes is intricately coupled to cleavage and polyadenylation, whereas transcription of small nucleolar (sno)/small nuclear (sn)RNA genes is terminated by the RNA-binding proteins Nrd1, Nab3 and Sen1. The existence of an Nrd1-like pathway in humans has not yet been demonstrated. Using the U1 and U2 genes as models, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 64 publications
3
60
1
Order By: Relevance
“…Since inhibition of NELF, Integrator and P-TEFb all resulted in defective 3 0 processing and termination of the U1 gene (Figs 2 and 3), it is likely that these processes occur in a coordinated manner by a mechanism similar to that of protein-coding genes. This view is consistent with a recent study that suggested the coupling of transcription termination and 3 0 processing of U1 snRNA 39 .…”
Section: Discussionsupporting
confidence: 93%
“…Since inhibition of NELF, Integrator and P-TEFb all resulted in defective 3 0 processing and termination of the U1 gene (Figs 2 and 3), it is likely that these processes occur in a coordinated manner by a mechanism similar to that of protein-coding genes. This view is consistent with a recent study that suggested the coupling of transcription termination and 3 0 processing of U1 snRNA 39 .…”
Section: Discussionsupporting
confidence: 93%
“…No clear homologues or analogues of the Nrd1 and Nab3 components of the NNS complex have been described in metazoans. SETX is unlikely to be involved in transcription termination of genes encoding snRNAs because termination defects have not been seen in SETX-knockdown experiments 86,89 . Genes encoding snRNAs contain a conserved 13-16-nucleotide sequence element (termed the 3ʹ box) that is required both for 3ʹ end processing and for transcription termination.…”
Section: Miller's Chromatin Spreadingmentioning
confidence: 99%
“…As the INT complex is recruited through its interaction with the Ser7P CTD and recognizes the nascent RNA, the pattern of concurrent recognition of signals on the nascent RNA and the CTD is conserved for snRNA 3ʹ processing and termination. However, termination is unlikely to be triggered by cleavage of the nascent transcript through an XRN2-dependent torpedo mechanism 89 . Rather, release of the polymerase has been linked to the particular structure of these genes, with a nucleosome-depleted region that spans the whole transcription unit, and to the action of negative elongation factor (NELF), which is involved in promoter-proximal pausing for mRNA transcription 89,92 .…”
Section: Miller's Chromatin Spreadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of the human version is implicated in the neurodegenerative diseases ataxia oculomotor apraxia 2 (AOA2) and amyotrophic lateral sclerosis 4 (ALS4) (164, 165). The role of senataxin in the termination of small RNAs in mammals is unclear, especially given that the full NNS system seems poorly conserved and short noncoding transcripts tend to be carved out of larger precursor transcripts terminated by the conventional polyadenylation-coupled machinery (166). More recently, a role for senataxin in the unwinding of RNA hybridized to duplex DNA (R-loop) suggested a function for this protein in polyadenylation-coupled mRNA termination in mammalian cells (167).…”
Section: Connections To Cell Physiology: Yeast and Humansmentioning
confidence: 99%